Performance-driven facades: Analysis of natural cross-ventilation in an indoor environment with Fast Fluid Dynamics and apertures optimization based on a genetic algorithm. (August 2014) - Karagkouni, Chrysanthi (Sandy); Fatah gen Schieck, Ava; Tsigkari, Martha; Chronis, Angelos
One of the primary aims of performance-oriented design is to develop spaces that achieve acceptable levels of human comfort. Wind-induced airflow plays a significant role in improving occupants' comfort in a building. This paper explores the extent to which simulation and evaluation of natural airflow can potentially be a contributing parameter in the conception of performance-aware designs. The authors employed Fast Fluid Dynamics simulation to study the natural ventilation performance of a pavilion and a genetic algorithm to optimize the shape of the pavilion's facades' openings. A performance analysis was conducted whereby an array of automated feedback loops carried out by a genetic algorithm produce a number of acceptable solutions. Hence the facade openings of these solutions are considered to be adequate to provide natural ventilation in the indoor environment. The study demonstrates the ability of the optimization model to yield design instances that fulfill a number of environmental criteria related to airflow and human comfort. In this light, the authors suggest that the aforementioned method can be used as an experimentation platform to influence and guide the designer during the initial stages of the design process towards a more performance-driven solution.